Ion Conductivity Enhancement in Anti‐Spinel Li3OBr with Intrinsic Vacancies. Issue 3 (22nd November 2018) - Hussain, Fiaz; Li, Pai; Li, Zhenyu; Yang, Jinlong
Abstract: Solid electrolytes are expected to play an important role in modern electrochemical energy storage technologies. However, it is still very challenging to achieve a high Li‐ion conductivity in solid electrolytes. In this study, an intrinsic vacancy induced ion conductivity enhancement in a recently synthesized anti‐spinel structure of Li3 OBr compared with its anti‐perovskite phase is reported. With a high stability, the intrinsic defective structure of anti‐spinel Li3 OBr contains a high concentration of octahedral vacancies. Ab initio molecular dynamic simulations confirm that octahedral vacancies can lead to an extraordinarily high Li mobility (0.136 mS cm −1 at room temperature) in anti‐spinel Li3 OBr. Such an ion conductivity enhancement mechanism opens a new avenue in solid electrolyte material design. Abstract : Anti‐spinel Li3 OBr as a promising solid electrolyte is studied from first principles and compared with anti‐perovskite Li3 OBr. Anti‐spinel Li3 OBr is more stable than its anti‐perovskite phase with a similar or even much lower vacancy concentration. Extraordinarily high Li conductivity is predicted for anti‐spinel Li3 OBr, which is determined by its high concentration of intrinsic vacancies.